Iron oxide nanoparticles as heterogeneous electro-Fenton catalysts for the removal of AR18 azo dye. Issue 16 (15th July 2020) - Ben Hafaiedh, Nouha; Fourcade, Florence; Bellakhal, Nizar; Amrane, Abdeltif
ABSTRACT: Heterogeneous electro-Fenton mineralization of Acid Red 18 (AR18) in aqueous solution was studied with magnetite Fe3 O4 (MNPs) and haematite Fe2 O3 (HNPs) nanoparticles as catalysts. High mineralization yields of AR18 were obtained with magnetite, 81% TOC removal after 180 min of electrolysis in 40 mg L −1 Fe3 O4, pH 3.0, at 50 mA of current intensity and in 50 mM Na2 SO4 . In order to explain the obtained mineralization yield achieved with MNPs, the quantification of hydrogen peroxide (H2 O2 ), hydroxyl radical (OH) and iron leaching were performed at 50 and 100 mA. From the high iron concentration found in the bulk solution and the slight impact of the catalyst mass concentration on TOC removal, the formation of hydroxyl radicals occurs mainly through homogeneous process. In the presence of hydroxyl radical scavenger, degradation remained total after 15 min showing the involvement of a direct electrochemical oxidation of the dye at the electrode surface. The hydroxyl radical oxidation is responsible for at least 50% of mineralization. GRAPHICAL ABSTRACT: